KERAGAMAN JENIS LALAT BUAH PADA BEBERAPA TANAMAN BUAH-BUAHAN DI KABUPATEN GOWA SULAWESI SELATAN - Yulis Sayang; Vien Sartika Dewi; H. Hamziah (LP4MK STKIP PGRI Lubuklinggau, 2022)
The aim of the study was to determine the diversity of fruit fly species (Bactrocera spp.) found in fruit trees in the lowlands Bontomarannu and highlands Tinggimoncong of Gowa Regency, South Sulawesi. The research took place for five months, starting from February to July 2020 which was carried out in two stages. The first stage was to fruit attacked by fruit flies and then put them in a plastic jar filled with sterile fine sand. The jar is covered with gauze and left until a cocoon is formed and an adult insect is born. Adult insects were transferred to petri dishes containing cork and had been smeared with honey as food for fruit flies. The population of adult insects was counted and then identified using a microscope. The second stage is setting traps containing attractant Methyl Eugonol for seven days on fruit plants. Observations were made daily on trapped fruit flies. The attractants in the traps were updated daily for subsequent observations for seven days. Fruit flies were brought to the laboratory for identification using a microscope. The identification results showed that there were five species of fruit flies namely B. papajae, B. carambolae, B. umbrosa, B. occipitalis and B. Cucurbitae.